Pengelompokkan Kabupaten/Kota Berdasarkan Jumlah Kasus Penderita Penyakit Menular di Jawa Tengah Tahun 2022 Menggunakan Analisis Cluster has been accepted - Avinda Lutfi Anggraini Putri Buana; Nisrina Aulia Salsabila; Sri Pingit Wulandari (Syntax Idea)
Infectious diseases, such as measles, AIDS, leprosy, leptospirosis, acute respiratory infections (ARI), and pneumonia, are still major health problems in Central Java Province, Indonesia. Factors such as population density, community mobility, environmental conditions, and socio-economic inequality influence the pattern of disease spread. Each district/city has unique characteristics in dealing with the spread of infectious diseases, thus requiring a region-specific policy approach. This study uses cluster analysis, a multivariate statistical technique that aims to group regions based on similarities in the number of infectious disease cases in 2022. Two clustering methods were used: complete linkage for the hierarchical approach and K-means for the non-hierarchical approach. Data on the number of infectious disease cases in Central Java Province in 2022 showed high variation in ARI and pneumonia, with values that were quite large and far from zero. In contrast, measles, AIDS, leprosy, and leptospirosis have low variation, with standard deviation values close to the mean, these data meet the assumptions of cluster analysis, namely multivariate normal distribution and dependence. The clustering method used consisted of two approaches: hierarchical clustering using the complete linkage method, districts were grouped into five clusters, and non-hierarchical clustering (k-means) resulted in the same grouping of five clusters.